Impact of Ultrasound-Guided Deep Serratus Anterior Plane Block Combined With Dexmedetomidine as an Adjuvant to Ropivacaine Inpatient Quality of Recovery Scores Undergoing Modified Radical Mastectomy: A Randomized Controlled Trial - Wu, Yu; Kang, Yuling; Li, Yanli; Fu, Bohan (Frontiers in Oncology, 2022)
Background: Breast cancer has overtaken lung cancer as the most commonly diagnosed malignancy and is the leading cause of cancer-related death in women. Previous reports suggested that Ultrasound-guided deep serratus anterior plane block (dSAPB) provided effective blockade to reduce pain after modified radical mastectomy for breast cancer. In fact, despite the use of long-acting local anesthetic agents, the patient's pain cannot completely be eliminated due to the short duration of anesthesia. Dexmedetomidine as an adjuvant to local anesthetics may prolong the duration of peripheral nerve block. However, no study has investigated the role of dSAPB with dexmedetomidine in the quality of recovery scores undergoing modifiedradical mastectomy. Material and Methods: Ultrasound-guided dSAPB combined with 30 mL of 0.375% ropivacaine or 30 mL of 0.375% ropivacaine with dexmedetomidine (1ug/kg) was administrated before anesthesia at the 4th to 5th ribs of the axillary midline. The primary outcome was quality of recovery, measured 24 h postoperatively using the QoR-15. Secondary outcomes were the VAS scores at rest and movement at 1, 6, 12, 24, and 48 h after surgery, 48h sufentanil consumption postoperatively, the incidence of postoperative nausea and vomiting (PONV), SAPB-related adverse events, and patient satisfaction with pain management. Results Eventually,73 participants (36 in Group R and 37 in Group RD) were included for final analysis, with age, BMI and median preoperative global QoR-15 score (IQR, 127[123.25-131] vs 126[121-130], p=0.662). The median postoperative global QoR-15 score(IQR, 107[103-112] vs 109.5[107-114], P=0.016), VAS score in rest at 12th hour (IQR, 1[1-2] vs 1[1-2], P=0.033), and VAS score in movement at 12th hour (IQR, 2[1-3] vs 2[1-3], P=0.014), at 24th hour (IQR, 3[2-3] vs 3[2-3], P=0.040), Median sufentanil rescues consumption(IQR, 14[12-17 vs 14[12-15],p=0.022] of Group RD were significantly lower than those of the Group R. Patient satisfaction score (SD, 8.28[0.70] vs 8.62[0.59],p=0.024) of Group RD were significantly higher than those of the Group R. Conclusion The ultrasound-guided dSAPB combined with dexmedetomidine plus ropivacaine may improve the QoR-15 in patients undergoing modifiedradical mastectomy. Furthermore, participants in the ropivacaine with DEX group met the superior pain relief in the early postoperative period, reduced the postoperative cumulative opioid consumption.